Different domiciles in online learning during the COVID-19 pandemic - Ahadin; Safiah, Intan; Yunus, Muhammad; Suartama, I Kadek; Solehudin, Mohammad; Hastuti, Wiwik Dwi (Journal of Education and e-Learning Research, 2023)
This study aims to determine differences in students’ perceptions, participation and satisfaction with online learning in terms of differences in residence namely in villages and cities. This study used comparative survey research. The research data sources were 597 Indonesian students from three regions namely western, central and eastern Indonesia. Data were collected using a questionnaire, then analysed using one-way multivariate analysis of variance assisted by the Statistical Package for the Social Sciences. The results of this study are as follows: (1) there are differences in perceptions of online learning during the COVID-19 period between students who come from villages and cities; (2) there are differences in participation in the online learning process during the COVID-19 period between students from rural and urban backgrounds and (3) there are differences in student satisfaction with online learning in terms of village and city backgrounds. The conclusion of this study is that students’ perceptions, participation and satisfaction with online learning are better in cities than in villages. The implications of this research require the attention of the government and academics to find steps to overcome online learning problems especially in rural areas.